STATIONARITY OF EXTREME STREAMFLOW TIME SERIES FOR FLOOD CONTROL OPERATION IN HYDROPOWER RESERVOIRS - Chan, Priscilla Dafne; Costa, Fernanda da Serra; Damázio, Jorge Machado; Rotunno Filho, Otto Correa (Cadernos do IME - Série Estatística, 2020)
DOI: 10.12957/cadest.2019.50174 The Brazilian Power Sector consider flood prevention in the operation by reserving during the rainy season empty volumes in its hydropower reservoirs. The currently used flood control methodology assumes seasonal stationarity for the naturalized daily streamflow records calculated by the Brazilian National Operator System (NOS/ONS). Considering that climatic and/or land uses and occupation changes may be altering hydrological regime, this article investigates the stationarity of maximum annual streamflow time series of duration compatible with flood events at the hydropower plants located in the Paraná river basin. Keywords: Statistical Tests, Extreme Streamflow Time Series Stationarity, Hydropower, Flood Control Studies.